2020
DOI: 10.1590/1980-5373-mr-2020-0036
|View full text |Cite
|
Sign up to set email alerts
|

Response of a DIN 18MnCrSiMo6-4 Continuous Cooling Bainitic Steel to Plasma Nitriding with a Nitrogen Rich Gas Composition

Abstract: The use of continuous cooling bainitic steels can provide a more energy efficient manufacturing route. However, for their use in mechanical components like gears, it is necessary to improve their surface properties without impacting the core properties to guarantee reliable mechanical performance. The effect of temperature and time on the plasma nitriding response of a DIN 18MnCrSiMo6-4 steel was investigated. The plasma nitriding was performed for 3, 6 and 9 hours, at 400, 450, 500 and 550 °C, using a gas mix… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
28
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 10 publications
(31 citation statements)
references
References 24 publications
2
28
0
1
Order By: Relevance
“…27 . The case depth increases with increasing time, temperature and nitrogen concentration as expected for diffusion-controlled growth 16,17 . On the other hand, Alsaran et al 17 had previously tried to explain the increase in the depth of the nitrided layer by increasing the ratio of hydrogen to nitrogen.…”
Section: Modification Of Surface Properties After Plasma Nitridingmentioning
confidence: 56%
See 4 more Smart Citations
“…27 . The case depth increases with increasing time, temperature and nitrogen concentration as expected for diffusion-controlled growth 16,17 . On the other hand, Alsaran et al 17 had previously tried to explain the increase in the depth of the nitrided layer by increasing the ratio of hydrogen to nitrogen.…”
Section: Modification Of Surface Properties After Plasma Nitridingmentioning
confidence: 56%
“…The present work is a continuation of previous work entitled "Response of a DIN 18MnCrSiMo6-4 Continuous Cooling Bainitic Steel to Plasma Nitriding with a Nitrogen Rich Gas Composition" 16 . For the investigated treatment conditions it was found that the treatment temperature of 500 °C developed the best results; therefore, in this work we opted to use this temperature.…”
Section: Materials Under Investigation and Plasma Nitridingmentioning
confidence: 74%
See 3 more Smart Citations